2014
DOI: 10.1016/j.cell.2014.07.051
|View full text |Cite|
|
Sign up to set email alerts
|

Skeletal Muscle PGC-1α1 Modulates Kynurenine Metabolism and Mediates Resilience to Stress-Induced Depression

Abstract: Depression is a debilitating condition with a profound impact on quality of life for millions of people worldwide. Physical exercise is used as a treatment strategy for many patients, but the mechanisms that underlie its beneficial effects remain unknown. Here, we describe a mechanism by which skeletal muscle PGC-1α1 induced by exercise training changes kynurenine metabolism and protects from stress-induced depression. Activation of the PGC-1α1-PPARα/δ pathway increases skeletal muscle expression of kynurenine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
418
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(441 citation statements)
references
References 72 publications
20
418
1
2
Order By: Relevance
“…Increased expression of muscle-specific PGC-1a1 in transgenic mice is associated with greater resilience to chronic stress and stress-induced CNS inflammation. 50 Thus, there are several points at which exercise biology and accompanying dietary adjustments may interact directly or indirectly with host-microbe interactions in the gut (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of muscle-specific PGC-1a1 in transgenic mice is associated with greater resilience to chronic stress and stress-induced CNS inflammation. 50 Thus, there are several points at which exercise biology and accompanying dietary adjustments may interact directly or indirectly with host-microbe interactions in the gut (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a positive effect of n‐3 fatty acid enriched protein‐dense supplements could be implicated as in cachectic patients with pancreatic cancer n‐3 FA supplementation also increased physical activity level assessed by doubly labelled water independent of muscle mass 24. Next to exercise, n‐3 FA additionally stimulate the PGC‐1α‐PPARα/δ pathway in muscle resulting not only in enhanced muscle (fat) oxidative metabolism25 and decreased muscle fatigue, but also in enhanced conversion of peripheral kynurenine into kynurenic acid, which is unable to cross the blood–brain barrier 26. Reducing plasma kynurenine protects the brain by mediating resilience to stress induced depression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our data suggest that the production of H2O2 by Lactobacillus may be protective against the development of despair behavior by direct inhibition of IDO1 expression and decrease in the circulating level of kynurenine, a metabolite associated with depressive behavior (Fig. 11) 84,[172][173][174] .…”
Section: Putting the Data In Contextmentioning
confidence: 99%
“…7e). Evidence of dysregulation of this pathway in depressed patients, as well as its recently described role in the initiation of despair behaviors 84 , have made the tryptophankynurenine pathway particularly compelling as part of the potential mechanism mediating the microbiome effects on behavior. Intriguingly, a recent study 166 showed that Lactobacillus can directly modulate kynurenine metabolism, by inhibiting the pathway initiating enzyme IDO1 via production of reactive oxygen species (i.e.…”
Section: Treatment With a Lactobacillus Species Ameliorates Despair Bmentioning
confidence: 99%
See 1 more Smart Citation